The ethnography of prisons and penal confinement - Cunha, Manuela Ivone P. da (2014)
Centered on the ethnography of prisons and field research on penal confinement, this review maps out current developments and haracterizes them in relation to key themes that shaped earlier approaches. Further nternationalizing the ethnographic discussion on prisons by broadening the predominant focus on the United States and the English-speaking world, the review is organized around a main line of discussion: the prison–society relation and the articulation between intramural and extramural worlds. More or less apparent in field research, this articulation is addressed from different perspectives—within and across different scales and analytic frames— whether centered more on the workings of the institution or on prisoners and their social worlds, both within and outside walls.The porosity of prison boundaries, increasingly acknowledged, has also been problematized and ethnographically documented in different ways: from prison-in-context to interface approaches, bothmore reflexive and attuned to broader theoretical debates.